The Relationship between Organizational Culture and School Effectiveness of Schools under the Suantheppharat Theepthai Chaloemphrakiat School Network, Pathum Thani Secondary Educational Service Area Office. - มณีขัติย์ เขมจิรา; แก้วมงคล ทรงยศ; ประวัติรุ่งเรือง ปราศรัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
To study the level of 1) Examination of the level of organizational culture in educational institutions; 2) Investigation of the level of school effectiveness; and 3) Exploration of the relationship between organizational culture and school effectiveness in six schools. The sample consisted of 243 administrators and teachers. The research instrument was a five-point rating scale questionnaire, which have index of Item-Objective Congruence: IOC between.80-1 and have confidenc .95. The statistics used for data analysis were percentage, mean, standard deviation, and Pearson’s product–moment correlation coefficient. The findings revealed that: 1) The overall level of organizational culture of school administrators and teachers was at the highest level (x̄= 4.57, S.D. = 0.299). When considered by dimension, the highest mean score was found in the quality dimension, followed by the integrity dimension, while the lowest mean score was the organizational goal orientation dimension; however, all dimensions were still rated at the highest level. 2) The overall level of school effectiveness was also at the highest level (x̄= 4.55, S.D. = 0.219). The dimension with the highest mean score was the ability to produce students with high academic achievement, followed by the ability to develop students’ positive attitudes, whereas the lowest mean score was the ability to solve internal school problems. 3) The relationship between organizational culture and school effectiveness showed a strong positive correlation, which was statistically significant at the .01 level. The relationship was positive, and the overall level of opinion was at the highest level. (r = 0.862) When considering each dimension, the dimension with the highest correlation was decision-making, followed by empowerment (delegation of authority).